16 Developing cardiac magnetic resonance imaging in the live zebrafish. (17th November 2015) - Merrifield, GD; Mullin, J; Gallagher, L; Tucker, C; Jansen, MA; Denvir, M; Holmes, WM
Abstract : The zebrafish (Danio rerio) is an important model organism for biomedical research with many practical advantages over alternative rodent models. These include a short life cycle, simplicity of large-scale breeding and low maintenance costs which make the costs of large scale studies involving this organism far more timely and economic than is possible with rodents. It has also become of unique interest to cardiac researchers due to the regenerative nature of the heart upon injury. While the transparent embryonic zebrafish has been widely imaged in vivo using optical techniques, there is currently a lack of comparative imaging techniques for use in the opaque post-embryonic form. We have developed an MRI system capable of imaging adult zebrafish in vivo with recovery for serial imaging. To enable this a micro-imaging MRI coil was integrated within a custom flowcell system, designed to sustain and monitor an anaesthetised zebrafish during an MRI scan. Using this system we have produced a range of anatomical scans of the heart of the zebrafish and begun exploring advanced cinematic and diffusion MRI possibilities to investigate functional and microstructure properties of the heart. The success of our system allows for new avenues of zebrafish (or other small fish) research to be explored and also to improve scientific data return while exploiting the ethical and economic advantages of the zebrafish and MRI in biomedical research.